Unlocking Private Investment in Sustainable Infrastructure in Asia - Bhajan Grewal; Nella Hendriyetty; Iskandar Abdullaev; Chul Ju Kim; Naoyuki Yoshino; Eisa Khan Ayoob Ayoobi (Routledge, 2023)
Investment in infrastructure is essential for promoting economic growth, and while countries in Asia have enjoyed higher rates of gross domestic product growth in recent years, the region remains severely deficient in the scale and quality of sustainable infrastructure. Moreover, population growth and climate change continue to put increasing pressure on the need for strategic and farsighted development, calling for policy makers to reevaluate infrastructure governance to ensure sustainable economic growth. Currently, in developing Asia, most investment in infrastructure comes from the public sector. However, with growing fiscal deficits and other budgetary constraints, it is essential to develop alternative sources of investment for infrastructure projects. This presents opportunities to tap into the private sector, which can play an instrumental role in minimizing the funding gap through the development of stronger, more transparent public–private partnerships (PPPs) and incentivizing sustainable infrastructure investment. This book provides a scholarly discussion on the importance of PPPs and approaches to unlock private participation in infrastructure investment based on lessons from across Asia. Among the proposed schemes are government tax incentives, development-based land value capture strategy under PPP land pooling, Viability Gap Funds, Project Development Facilities, and other guarantees. The book aims to assess the impacts and future of sustainable infrastructure investments and examines the role of governments in mobilizing financial resources and new models for unlocking private investment in sustainable infrastructure. This book consists of fifteen original chapters on the experiences of the Central Asia Regional Economic Cooperation (CAREC) and a few other cases for promoting private investment in sustainable infrastructure. The fact that not much has been published previously on this theme makes this book a welcome and timely addition to the much needed knowledge on this subject. 'The Open Access version of this book, available at www.taylor fran cis.com, has been made available under a Creative Commons Attribution- Non- Commercial- No Derivatives 4.0 license.'
Keywords: 330; Economic Infrastructure; Infrastructure investment; Private Equity; Public Infrastructure Investment; Public-Private Partnership